Investigating the factors underlying adaptive functioning in autism in the EU‐AIMS Longitudinal European Autism Project. Issue 4 (11th February 2019) - Tillmann, Julian; San José Cáceres, Antonia; Chatham, Chris H.; Crawley, Daisy; Holt, Rosemary; Oakley, Bethany; Banaschewski, Tobias; Baron‐Cohen, Simon; Bölte, Sven; Buitelaar, Jan K.; Durston, Sarah; Ham, Lindsay; et al.
Scientific Abstract: Individuals with autism spectrum disorder (ASD) exhibit significant impairments in adaptive functioning that impact on their ability to meet the demands of everyday life. A recurrent finding is that there is a pronounced discrepancy between level of cognitive ability and adaptive functioning, and this is particularly prominent among higher‐ability individuals. However, the key clinical and demographic associations of these discrepancies remain unclear. This study included a sample of 417 children, adolescents, and adults with ASD as part of the EU‐AIMS LEAP cohort. We examined how age, sex, IQ, levels of ASD symptom and autistic trait severity and psychiatric symptomatology are associated with adaptive functioning as measured by the Vineland Adaptive Behavior Scales‐Second Edition and IQ‐adaptive functioning discrepancies. Older age, lower IQ and higher social‐communication symptoms were associated with lower adaptive functioning. Results also demonstrate that older age, higher IQ and higher social‐communication symptoms are associated with greater IQ‐adaptive functioning discrepancy scores. By contrast, sensory ASD symptoms, repetitive and restricted behaviors, as well as symptoms of attention deficit/hyperactivity disorder (ADHD), anxiety and depression, were not associated with adaptive functioning or IQ‐adaptive functioning discrepancy scores. These findings suggest that it is the core social communication problems that define ASD that contribute to adaptive function impairments that people with ASD experience. They show for the first time that sensory symptoms, repetitive behavior and associated psychiatric symptoms do not independently contribute to adaptive function impairments. Individuals with ASD require supportive interventions across the lifespan that take account of social‐communicative ASD symptom severity. Autism Res 2019, 12: 645–657 . © 2019 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. Lay summary: This study investigated key clinical and demographic associations of adaptive functioning impairments in individuals with autism. We found that older age, lower IQ and more severe social‐communicative symptoms, but not sensory or repetitive symptoms or co‐occurring psychiatric symptoms, are associated with lower adaptive functioning and greater ability‐adaptive function discrepancies. This suggests that interventions targeting adaptive skills acquisition should be flexible in their timing and intensity across developmental periods, levels of cognitive ability and take account of social‐communicative ASD symptom severity.